MULTIMODALITY OF JAPANESE BACKCHANNEL IN BEAUTY VLOG - Filia, Filia, Dr.; Muthia, Nilam Husna (International Review of Humanities Studies, 2024)
A backchannel is generally known as a response in a conversation that serves as a sign that the interlocutor is paying attention. In conversation, verbal backchannel speech can simultaneously occur with nonverbal gestures. Backchannel in conversations in digital content is often found. Beauty content from Hiro Beauty Channel shows that backchannel in beauty vlogs often occurs through verbal and nonverbal . Previous studies have researched the behaviour of backchannel usage (Cutrone, 2011; Nurjaleka, 2019; Bodur et al., 2022; Ramadhani, 2023) and the behaviour of gazing gestures (Walker, 2010). However, there has yet to be research about the multimodality of backchannels in conversations on digital content such as beauty vlogs. This research explains the pattern of backchannel usage in beauty vlogs, both from verbal and non-verbal modes. This study methodology uses conversational analysis (Sacks et al., 1974; Heritage, 2001) and multimodality (Mondada, 2018). This study's result is that the interlocutor's backchannel means that 'the interlocutor is listening' and 'the interlocutor asks the speaker to continue his speech'. Both imply that the interlocutor is paying attention to the speaker. The backchannel multimodality pattern in beauty vlogs consists of three main types, namely (i) verbal backchannel, (ii) verbal and nonverbal backchannel, and (iii) nonverbal backchannel. This study also shows that the preferred mode in providing backchannel in Japanese combines both verbal and nonverbal modes.